Tính D(x) + C(x) và nghiệm của nó biết: D(x) = 2x^2 + x – 3 – 3x^3 C(x) = 3 + 3x^3 – x^2 + x

Question

Tính D(x) + C(x) và nghiệm của nó biết:
D(x) = 2x^2 + x – 3 – 3x^3
C(x) = 3 + 3x^3 – x^2 + x

in progress 0
Ximena 13 phút 2021-09-17T10:33:52+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-17T10:35:09+00:00

    Đáp án:

     

    Giải thích các bước giải:

     ta có 

    D(x) + C(x) = $2x² + x – 3 – 3x³ + 3 + 3x³ – x² + x$

                      = $( -3x³ + 3x³) + (2x² – x²) + (x+x) + (3-3)$

                       = $0 + x² + 2x + 0 = x² + 2x$

    ta có 

    $x² + 2x = 0$

    $x.(x+2) = 0$

     \(\left[ \begin{array}{l}x=0\\x+2=0\end{array} \right.\) 

     \(\left[ \begin{array}{l}x=0\\x=-2\end{array} \right.\) 

    0
    2021-09-17T10:35:15+00:00

    $\text { Đáp án: }$

    ` D(x) + C(x) `

    ` = 2x² + x – 3 – 3x³ + 3 + 3x³ – x² + x `

    ` = –3x³ + 3x² + 2x² – x² + x + x – 3 + 3 `

    ` = x² + 2x `

    $\text { Để }$ ` D(x) + C(x) ` $\text { có nghiệm thì }$ ` D(x) + C(x) = 0 `

    ` => x² + 2x = 0 `

    ` => x.x + 2x = 0 `

    `=> x(x + 2) = 0 `

    ` => ` \(\left[ \begin{array}{l}x=0\\x+2=0\end{array} \right.\) 

    ` => \(\left[ \begin{array}{l}x=0\\x=-2\end{array} \right.\) 

    $\text { Vậy nghiệm của }$ ` D(x) + C(x) ` $\text { là 0 ; –2. }$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )